An Early Myelosuppression in the Acute Mouse Sepsis Is Partly Outcome-Dependent - Skirecki, Tomasz; Drechsler, Susanne; Jeznach, Aldona; Hoser, Grażyna; Jafarmadar, Mohammad; Kawiak, Jerzy; Osuchowski, Marcin F. (Frontiers in Immunology, 2021)
Adult hematopoietic stem and progenitor cells (HSPCs) respond to bacterial infections by expansion to myeloid cells. Sepsis impairs this process by suppressing differentiation of stem cells subsequently contributing to an ineffective immune response. Whether the magnitude of HSPCs impairment in sepsis is severity-dependent remains unknown. This study investigated dynamics of the HSPC immune-inflammatory response in the bone marrow, splenic and blood compartments in moribund and surviving septic mice. 12-week-old outbred CD-1 female mice (n=65) were subjected to a cecal ligation and puncture (CLP) sepsis, treated with antibiotics and fluid resuscitation, and stratified into predicted-to-die (P-DIE) and predicted-to-survive (P-SUR) cohorts for analysis. CLP strongly reduced the common myeloid and multipotent progenitors, short-and long-term hematopoietic stem cell (HSC) counts in the bone marrow; Lineage-ckit+Sca-1+ and short-term HSC suppression was greater in P-DIE versus P-SUR mice. A profound depletion of the common myeloid progenitors occurred in the blood (by 75%) and spleen (by 77%) of P-DIE. In P-SUR, most common circulating HSPCs subpopulations recovered to baseline by 72h post-CLP. Analysis of activated caspase-1/-3/-7 revealed an increased apoptotic (by 30%) but not pyroptotic signaling in the bone marrow HSCs of P-DIE mice. The bone marrow from P-DIE mice revealed spikes of IL-6 (by 5-fold), CXCL1/KC (15-fold), CCL3/MIP-1 (1.7-fold) and CCL2/MCP-1 (2.8-fold) versus P-SUR and control (TNF, IFN-, IL-1,-5,-10 remained unaltered). Summarizing, our findings demonstrate that an early sepsis-induced impairment of myelopoiesis is strongly outcome-dependent but varies among compartments. It is suggestive that the HSCPC loss is at least partly due to an increased apoptosis but not pyroptosis.